The joy of exploring gardens : 60 travel experiences to uplift and inspire - Armstrong, Kate (Travel writer) (Lonely Planet, 2023)
Discover 60 of the world's most spectacular gardens plus 120 travel ideas to ignite a love of outdoor spaces. Featuring the history of every botanical gem, beautiful photography and trip planning tips, this uplifting book explores the restorative effects of flora and fauna, and the joy to be experienced from each of the inspiring gardens inside it. Walk spellbinding nature trails at the Desert Botanical Garden in Arizona, US; wander the stone paths of Japan's infamous Kenroku-en Garden; or steal away to a subtropical retreat just off the coast from Glengarriff, Ireland. In-depth garden profiles, Q&As with experts, and personal accounts from writers who have experienced the magic of each destination accompany the mesmerising gardens inside this book, so that you can learn just why each idyllic sanctuary is so joyful.